THE EFFECT OF PRODUCT QUALITY, ONLINE SHOPPING EXPERIENCE, AND BRAND IMAGE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION AS A MEDIATION VARIABLE KAYLAA_KIDS CONSUMERS IN PAYAKUMBUH CITY - Geby Alfaren; Rose Rahmidani (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effect of Product quality , Online shopping experience, and Brand image on Customer loyalty through Customer satisfaction as a mediating variable among Kaylaa_ Kids consumers in Payakumbuh City. The population in this study consists of all Kaylaa_ Kids consumers who have purchased products. The sample size used was 100 respondents, with the sampling technique employing purposive sampling, specifically consumers who had made at least two purchases. The data used in this study is primary data obtained through the distribution of questionnaires using a Likert scale. Meanwhile, secondary data was obtained from reference books and internet sources. The analysis method used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS software. The results of the study indicate that Product quality, Online shopping experience, and Brand image have a positive and significant effect on Customer satisfaction and Customer loyalty. In addition, Customer satisfaction has been proven to mediate the relationship between Product quality, Online shopping experience, and Brand image on Customer loyalty among Kaylaa_ Kids consumers in Payakumbuh City.